1991
DOI: 10.1073/pnas.88.16.7425
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of mRNAs encoding Na+,K(+)-ATPase alpha- and beta-subunit isoforms within the rat central nervous system.

Abstract: We have used in situ hybridization histochemistry to analyze the subceilular distribution of mRNAs encoding Na,K-ATPase a-and /3-subunit isoforms in the rat central nervous system. Substantial differences in the cellspecific pattern ofexpression were found for the genes encoding three isoforms of the a subunit. Transcripts of al-subunit genewere detected in virtually all cell types and structures examined. Expression of a2-subunit mRNA was characteristic of glia, whereas a3-subunit transcripts were predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
144
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 32 publications
10
144
0
Order By: Relevance
“…30 We found a decrease in mRNA levels for two subunits of the sodium/potassium-specific ATPase, Atp1a2 and Atp1b2, a combination predominantly found in glia. 31 Together with a concomitant downregulation of glial fibrillary acidic protein (Gfap), these genes may reflect gliaspecific alterations in the amygdala. Studies of cerebellar tissue from AA rats have demonstrated downregulated Gfap expression after long-term ethanol consumption, 32 while a cDNA array study of cortical tissue from human alcoholics identified cytoskeleton-related genes, in particular myelin-associated genes and Gfap, as the most prominent dysregulations.…”
Section: Discussionmentioning
confidence: 99%
“…30 We found a decrease in mRNA levels for two subunits of the sodium/potassium-specific ATPase, Atp1a2 and Atp1b2, a combination predominantly found in glia. 31 Together with a concomitant downregulation of glial fibrillary acidic protein (Gfap), these genes may reflect gliaspecific alterations in the amygdala. Studies of cerebellar tissue from AA rats have demonstrated downregulated Gfap expression after long-term ethanol consumption, 32 while a cDNA array study of cortical tissue from human alcoholics identified cytoskeleton-related genes, in particular myelin-associated genes and Gfap, as the most prominent dysregulations.…”
Section: Discussionmentioning
confidence: 99%
“…The third reason why the choroid plexuses are considered to the main site of formation should be the fact that the observations mentioned so far were accompanied by a significant number of concurrent studies that pointed to CSF formation by the choroid plexuses (Dandy, 1919;de Rougemont et al, 1960;Pollay et al, 1972;Weed, 1914;Welch, 1963) , and the secretory character of the choroid plexuses was confirmed by the application of the molecular biological methods during the past two decades (Brown et al, 2004;Johanson, 2008;Kanaka et al, 2001;Li et al, 2002;Oshio et al, 2005;Praetorius et al, 2004;Speake et al, 2003;Watts et al, 1991;Zlokovic et al, 1993).…”
Section: Criticism Of the Classic Hypothesis Of Cerebrospinal Fluid Fmentioning
confidence: 97%
“…The secretory character of choroid plexuses that involves pumps, cotransporters and antiporters, ion channels and aquaporins has been confirmed during the past 15 years by the application of molecular biological methods (Brown et al, 2004;Johanson, 2008;Kanaka et al, 2001;Li et al, 2002;Oshio et al, 2005;Praetorius et al, 2004;Speake et al, 2003;Watts et al, 1991;Zlokovic et al, 1993).…”
Section: The Site and The Way Of Cerebrospinal Fluid Formationmentioning
confidence: 98%
“…Localization of the a3/pl complex in neurons and nerve endings of the cochlea and vestibular system was not unexpected, as this subunit combination predominates in neurons (Hieber et al, 1991;Watts et al, 1991;Hsu and Guidotti, 1989;Urayama et al, 1989). Abundant Na,K-AlTase in neurons functions to reestablish the resting membrane potential after the generation of action potentials.…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms occur in an organand cell type-specific distribution in many tissues including kid-843 ney, brain, pineal gland, eye, liver, heart, and inner ear (Ryan and Watts, 1991;Watts et al, 1991;Sweadner, 1989). The physiological significance of the P-subunit remains obscure, but the a-subunit is thought to mediate catalytic activity.…”
Section: Introductionmentioning
confidence: 99%